221k views
3 votes
If 3t - 7 = 5t, then 6t =
A. 21
B. -7
C. -21
D. -42

1 Answer

4 votes

Answer:

C. -21 is your answer

Explanation:

Solve for t. Isolate the variable t in the first equation, then use the number gotten to solve the second equation.

3t - 7 = 5t

First, subtract 3t from both sides

3t (-3t) - 7 = 5t (-3t)

-7 = 5t - 3t

-7 = 2t

Isolate the variable (t). Divide 2 from both sides

(-7)/2 = (2t)/2

t = -7/2

t = -3.5

Plug in -3.5 for t in the second equation

6(t) =

6(-3.5) =

6(-3.5) = -21

C. -21 is your answer

~

User James Wilcox
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.